Application of oxytocin in ultrasound-guided percutaneous microwave ablation for treatment of hypervascular uterine fibroids: a preliminary report. (1st January 2019) - Fu, Yajie; Feng, Qingliang; Zhang, Shihong; Li, Yongjie
Abstract: Objective: This study evaluated the effect of oxytocin administration prior to microwave ablation (MWA) of hypervascular uterine fibroids. Methods: Thirty-two patients with 38 hypervascular uterine fibroids (Adler blood flow grade 3) were equally apportioned to receive intravenous oxytocin infusion (0.32 U/min) 20 min before ultrasound-guided percutaneous MWA, or no oxytocin (control). Changes in Adler blood supply grade and myoma volume were observed via color Doppler ultrasonography (CDU). All patients underwent quantitative ablation with single or double needle and microwave power 50 W (180 s). Treatment continued for those who did not reach the therapeutic goal. The myoma necrotic volume was evaluated by contrast-enhanced ultrasound. Ablation rate was the percent of MRI nonenhanced myoma volume after treatment, relative to myoma volume before treatment, 2 days after surgery. Results: Twenty minutes after oxytocin administration, CDU showed significant decrease of blood vessels in myomas, and Adler blood supply decreased from grade 3 to grade 1 or grade 0 in 10 and 9 myomas, respectively. Myoma volumes were reduced by 2.12 ± 0.24%. Necrotic volumes in the oxytocin (control) groups were 36.96 ± 2.78 cm 3 (22.68 ± 3.38 cm 3 ) and ablation rates were 95.4 ± 2.7% (85.7 ± 3.3%; t  = 12.68, 8.866, p  = 0.001, both). No serious complication was noted. Conclusion: Intravenous oxytocin administered before percutaneous MWA of hypervascular uterine fibroids can effectively block the blood supply vessels of the myoma, reduce the heat sink effect, and thereby increase the ablation volume and improve the local therapeutic effect.